Expression Patterns of Claudin Family Members During Tooth Development and the Role of Claudin-10 (Cldn10) in Cytodifferentiation of Stratum Intermedium - Wang, Xin; Chiba, Yuta; Jia, Lingling; Yoshizaki, Keigo; Saito, Kan; Yamada, Aya; Qin, Man; Fukumoto, Satoshi (Frontiers in Cell and Developmental Biology, 2020)
There is growing evidence showing that tight junctions play an important role in developing enamel. Claudins are one of the main components of tight junctions and may have pivotal functions in modulating various cellular events, such as regulating cell differentiation and proliferation. Mutations in CLDN10 of humans are associated with HELIX syndrome and cause enamel defects. However, current knowledge regarding the expression patterns of claudins and the function of Cldn10 during tooth development remains fragmented. This study aimed to analyze the expression patterns of claudin family members during tooth development and investigate the role of Cldn10 in amelogenesis. Using cap analysis gene expression of developing mouse tooth germs compared with that of the whole body, we found Cldn1 and Cldn10 were highly expressed in the tooth. Furthermore, single-cell RNA-sequence analysis using 7-day postnatal Krt14-RFP mouse incisors revealed Cldn1 and Cldn10 exhibited distinct expression patterns. Cldn10 has two isoforms, Cldn10a and Cldn10b, but only Cldn10b was expressed in the tooth. Immunostaining of developing tooth germs revealed claudin-10 was highly expressed in the inner enamel epithelium and stratum intermedium. We also found that overexpression of Cldn10 in the dental epithelial cell line SF2 induced alkaline phosphatase (Alpl) expression, a marker of maturated stratum intermedium. Our findings suggest that Cldn10 may be a novel stratum intermedium marker and play a role in cytodifferentiation of stratum intermedium.